2015
DOI: 10.1007/s00228-015-1854-7
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of mycophenolic acid in lung transplant recipients with and without cystic fibrosis

Abstract: The population PK model developed from our study successfully characterizes the absorption, distribution, and elimination of MPA in lung transplant recipients with or without CF disease. The decrease of MPA absorption and increase of both oral clearance (CL/F) and volume of distribution (V2/F and V3/F) in the CF patients would suggest the importance of MPA therapeutic monitoring for this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The principle of these models is to use first-order absorption with a lag-time chained to 2 or 3 compartment models. 68,[160][161][162]168,169,232,372,377,394,[547][548][549][550][551][552][553][554][555][556][557] More complex models have also been developed, such as the Erlang model that is a simplification of the gamma distribution in which the exponent is an integer that represents the number of virtual transit compartments that the drug has to cross to reach the central compartment, 368,392,558 but they did not always significantly improve the description of MPA profiles. 162 Finally, 1-, 2or more parallel gamma distributions have been able to describe accurately the multiple MPA absorption peaks seen with MMF in various clinical settings.…”
Section: Poppk Modeling Of Mpa Challenges With Modeling Mpa Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The principle of these models is to use first-order absorption with a lag-time chained to 2 or 3 compartment models. 68,[160][161][162]168,169,232,372,377,394,[547][548][549][550][551][552][553][554][555][556][557] More complex models have also been developed, such as the Erlang model that is a simplification of the gamma distribution in which the exponent is an integer that represents the number of virtual transit compartments that the drug has to cross to reach the central compartment, 368,392,558 but they did not always significantly improve the description of MPA profiles. 162 Finally, 1-, 2or more parallel gamma distributions have been able to describe accurately the multiple MPA absorption peaks seen with MMF in various clinical settings.…”
Section: Poppk Modeling Of Mpa Challenges With Modeling Mpa Absorptionmentioning
confidence: 99%
“…68,160,166,168,231,232,377,394,549,551,554,559,560,562 In some studies, the increase in body weight has been reported as increasing MPA oral clearance (CL), in adults 81,155,372,556 and in children. 563 In lung transplantation, CF clearly affects MPA oral bioavailability 162 or CL, 556 whereas when modeling concerned several types of organ transplants in the same analysis, the type of transplant also affected MPA bioavailability and CL. 162,563 Other covariates were more rarely reported, such as weight on the volume of distribution (Vd) in children 164 or creatinine clearance, albumin, sex on Vd, 550,551 MRP2 variants and EC-MPS or MMF formulations on CL, 392 or UGT1A9 variant on absorption and distribution of MPA from EC-MPS.…”
Section: Clinically Relevant Covariatesmentioning
confidence: 99%
See 1 more Smart Citation